The ‘Uncanny’ Eye - Zia, Mariam (Journal of Research in Humanities, 2023)
This paper draws from Sigmund Freud’s reference to the Evil Eye in his essay titled ‘The “Uncanny”’. The concept is expounded as part of the psycho-cultural space we live in. This paper argues that the eye and its association to, and importance in literature and art is not without purpose. It is entrapped in centuries of belief in the power of the eye as the possible/plausible instrument of change. The purpose of this paper is to suggest reasons for such faith in the powers of the eye and show the variety of imagery the concept of ‘sight’ allows us in the arts.